The nature of technological hazard - Hohenemser, C; Kates, R W; Slovic, P (Science (American Association for the Advancement of Science), 1983)
Technological hazards are evaluated in terms of quantitatively expressed physical, biological, and social descriptors. For each hazard a profile is constructed that considerably extends the conventional definition of risk. The profile, which is termed hazardousness, was understood in pilot experiments on perception and appeared to capture a large fraction of lay people's concern with hazard. It also suggests an orderly method for establishing priorities for the management of hazards.